Physiological characteristics of badminton match play - Faude, O.; Meyer, T.; Rosenberg, F.; Fries, M.; Huber, G. (European Journal of Applied Physiology, 2007)
The present study aimed at examining the physiological characteristics and metabolic demands of badminton single match play. Twelve internationally ranked badminton players (eight women and four men) performed an incremental treadmill test [VO2peak = 50.3 ± 4.1 ml min-1 kg-1 (women) and 61.8 ± 5.9 ml min-1 kg-1 (men), respectively]. On a separate day, they played a simulated badminton match of two 15 min with simultaneous gas exchange (breath-by-breath) and heart rate measurements. Additionally, blood lactate concentrations were determined before, after 15 min and at the end of the match. Furthermore, the duration of rallies and rests in between, the score as well as the number of shots per rally were recorded. A total of 630 rallies was analysed. Mean rally and rest duration were 5.5 ± 4.4 s and 11.4 ± 6.0 s, respectively, with an average 5.1 ± 3.9 shots played per rally. Mean oxygen uptake (VO2), heart rate (HR), and blood lactate concentrations during badminton matches were 39.6 ± 5.7 ml min-1 kg-1 (73.3% VO2peak), 169 ± 9 min-1 (89.0% HRpeak) and 1.9 ± 0.7 mmol l-1, respectively. For a single subject 95% confidence intervals for VO2 and HR during match play were on average 45.7-100.9% VO2peak and 78.3-99.8% HRpeak. High average intensity of badminton match play and considerable variability of several physiological variables demonstrate the importance of anaerobic alactacid and aerobic energy production in competitive badminton. A well-developed aerobic endurance capacity seems necessary for fast recovery between rallies or intensive training workouts.